Perilaku Wanita Pekerja Seksual Tidak Langsung Dalam Pencegahan IMS, HIV Dan AIDS Di Pub & Karaoke, Café Dan Diskotek Di Kota Semarang - Lokollo, Fitriana Yuliawati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Background: Indirect Sex Workers is girls who work an illegal as sexual workers, usually have main job but also make sexual transaction in night clubs. They are including of high risk group in spreading Sexual Transmitted Infection and HIV&AIDS cases. Purpose of the research is to describe Indirect Sex Workers behavior in order to prevent sexual transmitted infection and HIV&AIDS at pub & karaoke, café, and discoutiq in Semarang City. Method: The method of this research is qualitative study with case study design by purposive sampling for choosing the subject. The subject is Indirect Sex Workers in Semarang City especially at 1 pub & karaoke, 1 café, and 2 discoutiq in 2008-2009 with the inclusion criteria is she has experiences in sexual transaction with the client at night clubs in Semarang City for at least 2 person. Researcher use 6 subjects between 17-24 years old from around 60 Indirect Sex Workers in several locations. Result: The result of research show that the perceived of susceptibility of them regarding to vulnerability of IMS and HIV&AIDS is good. On the other hand, knowledge and practical in order to prevent Sexual Transmitted Infection and HIV&AIDS still low. Although they are agree with condom use as a good thing in order to prevent, but the fact is they are rare in using condom during every sexual activity. They have low bargain position for condom use negotiation. Also they still believe some myths about STI and HIV&AIDS. Meanwhile, support from peer group is a weak factor.